Association between non-insulin-based insulin resistance surrogate makers and Helicobacter pylori infection: a population-based study - Jiayu Qiu; Yueming Yu; Dingwei Liu; Sihai Chen; Youhua Wang; Jianxiang Peng; Jinliang Xie; Chengyun Wu; Feng Zhou; Hui Fang; Qirui Lai; Yong Xie (BMC Gastroenterology)
Abstract Background Current evidence on the associations between insulin resistance (IR) and Helicobacter pylori (H. pylori) infection remains limited. This study aimed to investigate the association between non-insulin-based surrogate markers of IR, including the triglyceride glucose (TyG) index, triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio, and the metabolic score for IR (METS-IR), and H. pylori infection in U.S. populations. Methods This cross-sectional study involving 939 U.S. participants from the National Health and Nutrition Examination Survey (NHANES) 1999–2000. The associations between three IR surrogate markers and H. pylori infection were respectively investigated using logistic regression model, restricted cubic spline (RCS) curve and subgroup analysis. Results Three IR surrogate markers levels were significantly elevated in H. pylori infection participants. There was a positive association between three IR surrogate markers and H. pylori infection, even after adjusting for potential confounding variables by three different models. In subgroup analysis, the adjusted association between three IR surrogate markers and H. pylori infection were more likely to be observed in female and Non-Hispanic White. Additionally, the RCS curve revealed a positive linear correlation between TyG index and H. pylori infection across all three models, and between METS-IR and H. pylori infection in Model 3. However, a positive nonlinear correlation was observed between TG/HDL-C ratio and H. pylori infection in all three models. Conclusions These findings suggest that non-insulin-based IR surrogate markers including TyG index, TG/HDL-C ratio, and METS-IR were all positively associated with H. pylori infection. These markers may serve as the potential indicators for identifying the risk of H. pylori infection in U.S. populations. Clinical trial number Not applicable.